TAX REVENUES ON ECONOMIC DEVELOPMENT IN NIGERIA (Journal of Global Accounting, 2024)
The study examined the effect of tax Revenue as a stimulus on economic development in Nigeria. The specific objective was to ascertain the effect of value added tax, company income tax, petroleum profit tax and personal income tax on the human development index of Nigeria. Ex-post facto research design was adopted for the study. Secondary data were collected from the Central Bank of Nigeria bulletin, the Federal Inland Revenue Service (FIRS) tax report, and the Nigerian Bureau of Statistics bulletin, covering a twenty-year period from 2004 to 2023. Descriptive statistical analysis was performed to summarise the data while Robust Least Squares (RLS) regression analysis was applied in the test of hypotheses at 5% significance level. The findings revealed that: value added tax and company income tax have a non-significant positive effect on the human development index of Nigeria (p-value > 0.05); petroleum profit tax has a negative and significant effect on the human development index of Nigeria (p-value < 0.05); and personal income tax has a positive and significant effect on the human development index of Nigeria (p-value < 0.05). In conclusion, effective utilization of tax revenues for public goods and services is crucial in enhancing the quality of life and achieving broader developmental goals. The study recommends among others that the National Assembly should consider revising the Personal Income Tax structure to increase progressivity, ensuring higher earners contribute more and also use the additional revenue to fund social security and welfare programs, enhancing the Human Development Index by reducing income inequality and improving public services.
Keywords: Company Income Tax; Human Development Index; Personal Income Tax; Petroleum Profit Tax; Value Added Tax; Economic Development